MANAGEMENT PROTOCOL OF MANDIBULAR FRACTURES AT PAKISTAN INSTITUTE OF MEDICAL SCIENCES, ISLAMABAD, PAKISTAN. - Ajmal, Samira; Khan, Muhammad Ayub; Jadoon, Huma; Malik, Saleem A. (Journal of Ayub Medical College Abbottabad, 2007)
Background: Maxillofacial trauma is very frequent and associated with a high incidence of mandibular fractures. Although there is universal agreement as to the treatment goals and basic therapeutic principles of reduction and stabilization, a variety of currently accepted treatment modalities indicate a lack of consensus. The authors evaluate the incidence, etiology, management and complications of 344 mandibular fractures in 228 patients treated in the Department of Plastic and Reconstructive Surgery at Pakistan Institute of Medical Sciences (PIMS), Islamabad, Pakistan, during a three year period. Indications and techniques for closed and open treatment of mandibular fractures are reviewed along with any complications of these fractures or their management. Methods: A total of 344 mandibular fractures in 228 patients were included in this study. The sex, age, etiology, presentation, fracture characteristics, associated injuries, various methods of management and any pre or postoperative complications were evaluated. Results: Although various devices and techniques have been used to treat these fractures, modern plate and screw fixation systems have proved to provide the best rigid stabilization, early mobility and associated with least complications. There was a satisfactory bone healing in all the patients and a minimal complication rate associated with open reduction and internal fixation (ORIF). Conclusion: Mandibular fractures occur with high frequency in road traffic accidents and interpersonal violence. They are among the most common types of facial fractures treated by the plastic surgeons. They must be managed carefully to maintain the function of the mandible, reestablish proper occlusion, and minimize secondary complications. Open reduction and internal fixation has proven to be the most effective method for treatment of mandibular fractures. Key Words: Maxillofacial; Trauma; Fracture; Mandible; Management